The combined effect of plasticizers and graphene on properties of poly(lactic acid) - da Silva J.A.* (2018)
© 2018 Wiley Periodicals, Inc.Poly(lactic acid)’s (PLA) mechanical and barrier properties depend on the solid-state morphology and crystallinity. To overcome those limitations, plasticizers and nanoparticles are added. Common plasticizers for PLA, such as poly(ethyleneglycol) (PEG) and dibutyl sebacate (DBS), as well as graphene, were used in this work. Therefore, the combined effects of such additions in PLA's mechanical, thermal, and electrical properties were evaluated. The relation between graphene concentration and dispersion was different when DBS or PEG was used. The best dispersion was observed with the lowest (0.25% wt) graphene concentration in the composites with DBS. When PEG was used as plasticizer, the highest (0.5% wt) concentrations of graphene resulted in good dispersion. The best Young's modulus results were observed in the nanocomposites with better graphene dispersion, but the presence of graphene agglomerates seemed to lower the charge transfer resistance, probably because they prevent the plasticizers’ diffusion to the surface and the formation of a second phase. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2018, 135, 46745.